Tetra-n-butylammonium bis(2,2-dicyanoethylene-1,1-dithiolato)palladium(II) - Kanganga, Nyasha (International Union of Crystallography, 2008)
In the title compound, (C(16)H(36)N)(2)[Pd(C(4)N(2)S(2))(2)], the Pd(II) center adopts a distorted square-planar geometry due to the four-membered chelate rings formed by coordination of the 2,2-dicyanoethylene-1,1-dithiolate (i-mnt) ligands [bite angle 75.0159 (17)°]. The bond distances in the coordinated i-mnt ligands indicate some delocalization of the π-system.